ANALISIS PERBANDINGAN PENGARUH ENDORSER TERHADAP KEPUTUSAN PEMBELIAN YANG DIMEDIASI OLEH BRAND AWARENESS - Hapsari, Tanti Prita; Saptyawati, Laksmindra (Journal Competency of Business, 2022)
This study examines and compares the effect of using an endorser on purchasing decisions mediated by brand awareness. The endorsers used consisted of celebrity endorsers and expert endorsers. The purpose of this study was to examine 1) the effect of using celebrity endorsers and expert endorsers on purchasing decisions, 2) the effects of using celebrity endorsers and expert endorsers on brand awareness, 3) the effect of brand awareness on purchasing decisions and 4) brand awareness mediates the influence of celebrity endorsers and expert endorser on purchasing decisions. Research on the use of endorsers is important to do to assist companies in making effective strategic policies related to advertising. The respondents selected and used in this study were women in the Special Region of Yogyakarta. The number of questionnaires used was 150 questionnaires, while data analysis was used to test the mediating variable using the path analysis method